Hyperreactio luteinalis associated with fetal hyperandrogenism and cystic hygroma - Ali Ghassa; Dema Adwan; Mhd Firas Safadi (Clinical Case Reports, 2022)
Abstract A 23‐year‐old woman with a gestational age of 17 weeks presented with abdominal pain. The ultrasound showed maternal hyperreactio luteinalis with fetal cystic hygroma. After termination of pregnancy, the female fetus showed masculinization features with muscular hypertrophy. The hyperreactio luteinalis regressed under hormonal suppression therapy.